Enhanced γ-aminobutyric acid levels promote degeneration of silk glands following spermidine supplementation in Bombyx mori - Brinda Goda Lakshmi Didugu; Anitha Mamillapalli (Amino Acids, 2025)
Abstract Silk glands are modified labial glands that produce silk which has immense commercial importance. Silk is extruded out in liquid form after which the glands undergo autophagy and apoptosis during larval to pupal transition. Biogenic amines, specially spermidine and γ-aminobutyric acid (GABA) are known to play an important role in autophagy. Yet, GABA is not identified in the silk glands till now and therefore its role in autophagy remains unknown. Current study aimed to evaluate role of biogenic amines in the autophagy of silk glands. Fifth instar silkworms were fed with control and spermidine supplemented mulberry leaves under controlled conditions. Qualitative and quantitative analysis of biogenic amines were analyzed in silk glands of control and spermidine fed groups at the end of feeding stage, spinning and pre-pupal stages. Biogenic amines were significantly decreased in the silk glands from feeding stage to non-feeding prepupal stages. Elevated levels of biogenic amines; putrescine, spermidine, and spermine were observed in silk glands at pre-pupal stage in the spermidine fed group. The unknown biogenic amine whose levels were significantly elevated during silk gland degeneration in both control and spermidine fed groups was identified as GABA by spectroscopic techniques. This is the first report of the identification of GABA in the silk glands of Bombyx mori which increased significantly following spermidine supplementation, resulting in elevated levels of calcium deposits, contributing to the early degeneration of the silk glands.